Republic of India Manufacturing Plan Implementation : A New Agenda--Improving the Competitiveness of the Textiles and Apparel Value Chain in India - World Bank (Washington, DC, 2015)
This set of reports on manufacturing plans implementation in India includes the following: (1) A new agenda. Improving the competitiveness of the textiles and apparel value chain in India report is structured as follows: section one sets out the context, describing trends in global markets and in the textiles and apparel supply chain in India; section two analyzes in detail the choke points that are hindering the growth of the latter; section three sets out a reform agenda to address them; and section four concludes. (2) Fast tracking Indias electronics manufacturing industry. Business environment and industrial policy examines the prospects for India to meet its potential. Drawing on extensive survey questionnaires and interviews with key industry players (both domestic and foreign) and relevant government agencies, this study identifies major challenges India-based companies face in engaging in electronics manufacturing. The analysis culminates in detailed policy suggestions for regulatory reform and support policies needed to unblock barriers to investment in this industry and to fast-track it’s upgrading through innovation. (3) Supply chain delays and uncertainty in India. The hidden constraint on manufacturing growth report provides the context of the freight and logistics industry in India; describes the headline impacts of its performance on manufacturing firms; explores variations in this impact and causes thereof; and concludes with a more detailed look at the reform agenda this motivates.